2013
DOI: 10.1101/gr.145557.112
|View full text |Cite
|
Sign up to set email alerts
|

Increasing frequencies of site-specific mutagenesis and gene targeting in Arabidopsis by manipulating DNA repair pathways

Abstract: Improved methods for engineering sequence-specific nucleases, including zinc finger nucleases (ZFNs) and TAL effector nucleases (TALENs), have made it possible to precisely modify plant genomes. However, the success of genome modification is largely dependent on the intrinsic activity of the engineered nucleases. In this study, we sought to enhance ZFNmediated targeted mutagenesis and gene targeting (GT) in Arabidopsis by manipulating DNA repair pathways. Using a ZFN that creates a double-strand break (DSB) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 44 publications
6
139
0
2
Order By: Relevance
“…Zinc finger nuclease (ZFN) and, more recently, transcription activator-like effector nuclease (TALEN) have been tested as tools for targeted plant gene editing. Several publications have reported successful modifications in native plant genes, but both methods are tedious, expensive, and with only a small number of genes modified so far (18)(19)(20)(21)(22)(23)(24)(25). In sharp contrast, we report specific modifications of seven genes in this study in the span of just a few months, demonstrating the extremely easy-to-use feature of the CRISPR/Cas system.…”
Section: Discussionmentioning
confidence: 58%
“…Zinc finger nuclease (ZFN) and, more recently, transcription activator-like effector nuclease (TALEN) have been tested as tools for targeted plant gene editing. Several publications have reported successful modifications in native plant genes, but both methods are tedious, expensive, and with only a small number of genes modified so far (18)(19)(20)(21)(22)(23)(24)(25). In sharp contrast, we report specific modifications of seven genes in this study in the span of just a few months, demonstrating the extremely easy-to-use feature of the CRISPR/Cas system.…”
Section: Discussionmentioning
confidence: 58%
“…The authors reported GT frequencies of more than 10% in most experiments (Shukla et al, 2009). Very recently, ZFN-mediated GT was documented in Arabidopsis (de Pater et al, 2012;Qi et al, 2013).…”
Section: Zinc Finger Nucleases: Fulfillment Of the Promisementioning
confidence: 97%
“…In plants, the same type of results was obtained when using ZFNs targeting the endogenous ADH1 locus in Arabidopsis thaliana. Knock-in was increased up to 16 times in the Atku70 mutant and 3 to 4 times in the Atlig4 and Atsmc6b mutants [100]. Higher rates of homology-driven knock-in were also observed in mammalian cells when using hCas9 fused to proteins involved in cell-cycle dynamics [101,102], allowing a low expression of the nuclease in G1 and a high expression during S/G2/M phases where HDR mediated repair is favored [103,104].…”
Section: Understanding and Controlling The Dna Repair Pathways Involvmentioning
confidence: 95%